Allogeneic Stem Cell Transplantation Combined With Transfusion of Mesenchymal Stem Cells in Primary Myelofibrosis: A Multicenter Retrospective Study - Wang, Qingyuan; Xu, Na; Wang, Yu; Zhang, Xi; Liu, Limin; Zhou, Huifen; Wang, Hong; Zhang, Xiang; Tang, Xiaowen; Fu, Chengcheng; Miao, Miao; Wu, Depei (Frontiers in Oncology, 2022)
Background Allogeneic stem cell transplantation (allo-SCT) remains the only effective curative therapy for primary myelofibrosis. Utilization and efficacy of allo-SCT are limited by lethal complications, including engraftment failure, and acute (aGVHD) and chronic graft-versus-host disease (cGVHD). Several clinical trials have explored the use of mesenchymal stem cells (MSCs) in allo-SCT to prevent hematopoietic stem cell (HSC) engraftment failure and control GVHD. Methods Clinical data of 17 patients with primary myelofibrosis who underwent allo-SCT combined with ex vivo expanded MSC transfusion in four centers from February 2011 to December 2018 were retrospectively analyzed. Results All patients received myeloablative conditioning regimen. The median number of transplanted nucleated cells (NCs) per kilogram body weight was 11.18 × 108 (range: 2.63–16.75 × 108), and the median number of CD34+ cells was 4.72 × 106 (range: 1.32–8.4 × 106). MSCs were transfused on the day of transplant or on day 7 after transplant. The median MSC infusion number was 6.5 × 106 (range: 0.011–65 × 106). None of the patients experienced primary or secondary graft failure in the study. The median time to neutrophil engraftment was 13 days (range: 11–22 days), and the median time to platelet engraftment was 21 days (range: 12–184 days). The median follow-up time was 40.3 months (range: 1.8–127.8 months). The estimated relapse-free survival (RFS) at 5 years was 79.1%, and overall survival (OS) at 5 years was 64.7%. Analysis showed that the cumulative incidence of aGVHD grade II to IV was 36% (95% CI: 8%–55%) and that of grade III to IV was 26% (95% CI: 0%–45%) at day 100. The cumulative incidence of overall cGVHD at 2 years for the entire study population was 63% (95% CI: 26%–81%). The cumulative incidence of moderate to severe cGVHD at 2 years was 17% (95% CI: 0%–42%). Seven patients died during the study, with 5 patients succumbing from non‐relapse causes and 2 from disease relapse. Conclusion The findings of the study indicate that allo-SCT combined with MSC transfusion may represent an effective treatment option for primary myelofibrosis.